(untitled) (Asian Education Studies, 2018)
This paper reviewed a one-term experiment made with a new writing teaching method, form-focused instruction(FFI), in the flipped classroom model) used in teaching English writing to 102 first-year non-English-majored graduate students from Yangtze University as participants. The participants in the control group, CG, were taught by the traditional English writing method: grammar-translation teaching method and the participants in the treatment group, TG, were taught by the new English writing teaching method of FFI. The results showed that 1) Compared with a traditional English writing approach for CG, FFI in the flipped classroom model used in teaching English writing for TG did a better job in enhancing students’ English writing ability; 2) There were significant differences between males in CG and TG, and females in CG and TG; 3) Participates in TG held positive opinions towards FFI in the flipped classroom model in English writing.